2020
DOI: 10.1108/ijbm-04-2020-0191
|View full text |Cite
|
Sign up to set email alerts
|

Customer reactions to bank hypocrisy: the moderating role of customer–company identification and brand equity

Abstract: PurposeThe purpose of this study was to investigate the effect of perceived corporate hypocrisy on customer mistreatment behaviors within the banking industry and the moderating effects of customer–company identification (CCI) and brand equity on the hypocrisy-mistreatment behavior relationship.Design/methodology/approachUsing multistage sampling, 567 South Korean banking service users participated in an online survey. Structural equation modeling (confirmatory factor analysis) and hierarchical regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 94 publications
(140 reference statements)
0
27
0
Order By: Relevance
“…They may also make it difficult for the sector to attract new employees (Willems, 2020). Furthermore, two stereotypes relate to results found in previous research: the shark stereotype can be considered an individual measure of corporate greed (Caruana et al , 2018), corporate hypocrite (Hur and Kim, 2020) or unethical sales practices (Tosun, 2020); the subordinate stereotype can relate to customer overconfidence, which is to say customers who do not seek advice when making investment decisions (Lewis, 2018). Overall, negative stereotypes may reflect a global loss of trust and commitment from the customers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…They may also make it difficult for the sector to attract new employees (Willems, 2020). Furthermore, two stereotypes relate to results found in previous research: the shark stereotype can be considered an individual measure of corporate greed (Caruana et al , 2018), corporate hypocrite (Hur and Kim, 2020) or unethical sales practices (Tosun, 2020); the subordinate stereotype can relate to customer overconfidence, which is to say customers who do not seek advice when making investment decisions (Lewis, 2018). Overall, negative stereotypes may reflect a global loss of trust and commitment from the customers.…”
Section: Discussionmentioning
confidence: 84%
“…The studies that came closest to examining professional stereotypes were conducted by Willems (2020) on public servants, including bankers, by Lazarus (2012), who looked at four “banker figures,” and by Bienfait (2014), who studied the stereotype of the telephone advisor (banking by telephone). Although the literature shows that some customers fail to seek advice (Lewis, 2018) or fear corporate greed (Caruana et al , 2018), corporate hypocrisy (Hur and Kim, 2020), and unethical sales practices (Tosun, 2020), it still does not give an exhaustive scientific examination of the banker stereotype.…”
Section: Introductionmentioning
confidence: 99%
“…, 2018; Salem et al. , 2019), as well as the danger of negative customer experiences going viral (Hur and Kim, 2020), which also explains why the cluster on customer satisfaction and loyalty (Cluster 3) has also overtaken the cluster on consumer behavior (Cluster 2) in banking and financial services research in IJBM . That is to say, the emergence and virality of service failure in the digital era have accentuated the challenge and importance of customer retention and satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…With the democratization of banking and financial services in the digital era, the cluster on service failure and recovery (Cluster 6) has also proliferated, which signals the emergence of new issues encountered by customers of banking and financial services, especially that over the Internet (e.g. cybersecurity, privacy) (Marafon et al, 2018;Salem et al, 2019), as well as the danger of negative customer experiences going viral (Hur and Kim, 2020), which also explains why the cluster on customer satisfaction and loyalty (Cluster 3) has also overtaken the cluster on consumer behavior (Cluster 2) in banking and financial services research in IJBM. That is to say, the emergence and virality of service failure in the digital era have accentuated the challenge and importance of customer retention and satisfaction.…”
Section: Intellectual Structure Of Ijbmmentioning
confidence: 99%
“…In addition to studying the mediational effect of three needs, we also examine the boundary condition of brand passion formation by studying the moderating effect of customer–company identification (CCI) into the relationship between strategic CSR‐brand fit and psychological needs satisfaction through the lens of social identity theory (SIT). Prior studies guided by SIT suggest that customers will more likely to be identified with those firms which help them build their social identities (Hur & Kim, 2020; Lafferty et al, 2016; Pérez & Rodríguez del Bosque, 2013) and the firm's CSR initiative is the one important way which contributes largely to building CCI (Yang et al, 2019). Swimberghe and Wooldridge (2014); noted that high CCI can satisfy customers' belongingness needs and strengthened active brand loyalty through the firm's CSR efforts.…”
Section: Introductionmentioning
confidence: 99%